Метод захисту та відтворення інформації засобами Ateb-функцій - Грицик, В.В.; Дронюк, І.М.; Назаркевич, М.А. (Видавничий дім "Академперіодика" НАН України, 2008)
A method of defense of information in acts that can be used in the pre-print preparation of a model is developed. The method can be used for paper and electronic carriers and is based on the application of networks of the unique form that are the plots of solutions of a system of nonlinear differential equations. These solutions are presented in terms of the orthonormalized system of periodic Ateb-functions. On this basis, a method for the identification of acts in an array is proposed.